Association of intraindividual differences in estimated glomerular filtration rates based on cystatin C and creatinine with dementia: A cohort study of the UK Biobank - Zhiyi Mao; Yuwei Peng; Ruilang Lin; Xinyue Guo; Xiaorui Cui; Yongfu Yu; Xueying Zheng (PLoS ONE, 2026)
Background Dementia is a leading cause of cognitive decline, with Alzheimer’s disease (AD) and vascular dementia (VaD) being the most common subtypes. The intraindividual difference between the estimated glomerular filtration rate based on cystatin C and creatinine (eGFR diff ) may serve as an indicator of the overall health status of an individual. However, the relationships between the eGFR diff and dementia risk, dementia subtypes, dementia-related neuroimaging changes, and cognitive functions remain unclear. Methods This study analysed data from over 450,000 participants in the UK Biobank who were followed for up to 15 years. The estimated glomerular filtration rate based on cystatin C (eGFR cys ) and creatinine (eGFR cr ) was calculated using the CKD-EPI equation, and eGFR diff was defined as the difference between these values (eGFR diff = eGFR cys − eGFR cr ). Multivariate Cox regression models were used to evaluate the associations between the eGFR diff and all-cause dementia (ACD), AD, and VaD, whereas cross-sectional analysis were used to examine the relationship among the eGFR diff , dementia-related neuroimaging changes, and cognitive functions. Results Over a median follow-up of 13.5 years, 8,710 participants developed dementia, including 3,910 with AD and 1,893 with VaD. Each one standard deviation increase in eGFR diff was associated with a reduced risk of dementia, with hazard ratios (95% confidence intervals) of 0.92 (0.90–0.94) for ACD, 0.94 (0.91–0.98) for AD, and 0.90 (0.85–0.94) for VaD. A negative eGFR diff was associated with adverse neuroimaging changes, including lower total brain and gray matter volumes and higher white matter hyperintensities. Additionally, a negative eGFR diff was associated with poorer performance across multiple cognitive domains. Conclusion A negative eGFR diff was associated with an increased risk of dementia, adverse neuroimaging outcomes, and cognitive decline. These findings suggest that the eGFR diff might be considered a potential associative indicator for dementia and cognitive impairment, suggesting potential clinical value in risk assessment and early intervention strategies.